Kan het misschien iets scherper?: Christelijke dogmatiek als protestantse bijdrage aan het oecumenische gesprek - Reeling Brouwer, Rinse (Tijdschrift voor theologie, 2013)
A dogmatics which aims to contribute to a new consideration within the whole of ecumenicity from a specific denominational point of view will ignore the less urgent questions and older ways of thinking that have become problematic, and try to emphasise its own commitment in a new situation. Christelijke Dogmatiek may have all the hallmarks of a Dutch reformed theology, but is remarkably reticent on certain points close to the authors’ hearts. They go to such lengths to communicate the reformational approach to justification with such reservations that the devotion to nothing but the received Word is smothered in circumspection. The pneumatological embedding of their approach of the Bible, for example, makes their explanation that Scripture is not just a function of the interpretative interests of the community of faith, almost seem like an afterthought. It makes it seem as if Israel and the church are burdened less by the fact that they are chosen than by the external stress of diminishing social acceptance. Thus, with attention to a phenomenological perspective on humanity as creatures and believers, anthropology and the doctrine of sin fail to clarify Jesus Christ’s role as not just the God of the covenant speaking to the people, but also as the human partner in the covenant. A more outspoken position would have allowed for a rather more critical response here.